Study the Correlation Between Serum Intact Parathyroid Hormone Levels and Erythropoiesis Resistance Index (ER) in Patients on Maintenance Hemodialysis (MHD) (Medical Forum Monthly, 2024)
Objective: To find the correlation between serum intact parathyroid hormone levels and erythropoiesis resistance index (ER) in patients on Maintenance Hemodialysis (MHD) Study Design: Analytical / Cross-Sectional Study Place and Duration of Study: This study was conducted at the Dialysis Center and Nephrology OPD of Idris Teaching Hospital, Sialkot Medical College Sialkot from May 2018 to May 2019. Materials and Methods: About 70 chronic kidney disease patients presenting to the Dialysis Unit and OPD Department and fulfilling the selection criteria were enrolled. Serum iPTH levels were measured by taking a fasting venous sample. Hb was calculated from CBC. ERI was calculated by the formula mentioned earlier. Data were used to calculate the correlation between iPTH levels and ERI using Karl Pearson coefficient with statistically p-value <0.05. Data were stratified for Age, Gender, BMI and Duration of MHD to address effect modifiers. Post stratification Pearson’s correlation was applied with p-value < 0.05 was considered as significant. Results: The mean age of the patients was 43.82±15.89 years. 16(22.9%) of the patients had age 16-35 years, while 32(45.7%) and 22(31.4%) of patients had ages between 36-55 and >55 years respectively. Gender distribution showed that 48(68.6%) were males while 22(31.4%) were females. The mean duration of patients on maintenance hemodialysis was 5.45±1.12 years. The mean BMI of patients on maintenance hemodialysis was 28.3±6.36.The mean iPTH and ERI was 67.54±22.69 and 9.11±4.24 respectively. Conclusion: It was concluded that intact parathyroid hormone levels (iPTH) is positively correlated with erythropoiesis resistance index (ERI) in patients on Maintenance Hemodialysis (MHD).